Personality traits and relationship perceptions in coach-athlete dyads: Do opposites really attract? - Jackson, B.; Dimmock, J.; Gucciardi, Daniel; Grove, J. (Elsevier BV, 2011)
Objectives: The resurgence in mainstream personality research over recent decades has providedsubstantive insight into the way in which dyad members’ traits shape their relational experiences.Surprisingly, researchers are yet to examine these issues within coacheathlete contexts, and the present study sought to explore how Big Five traits predicted relationship commitment and relatedness (i.e., closeness, trust) for members of established coacheathlete dyads.Methods: Ninety one athletes (Mage ¼ 20.76, SD ¼ 3.55) and their coaches (n ¼ 91, Mage ¼ 37.33,SD ¼ 10.17) reported their own Big Five as well as their relationship commitment and relatednessperceptions. Analyses were conducted using actorepartner interdependence models due to the nonindependence in coach and athlete data.Results: Accounting for demographic variables, analyses revealed that individuals’ relationship perceptions were underpinned by their own and their partners’ traits, as well as the extent to which theirrespective traits were concordant. In particular, greater dissimilarity between partners’ extraversion andopenness was associated with reduced commitment and relatedness for coaches and athletes. Positiveactor effects emerged for commitment (i.e., agreeableness, conscientiousness, extraversion) and relatedness (i.e., agreeableness, extraversion), and partner effects revealed that dyad members reportedfavorable outcomes when their partner was highly conscientious and/or agreeable. The potentialmoderating effect of one’s role in the dyad was also examined.Conclusions: Consistent with mainstream relationship settings, the Big Five model may provide important insight into dyadic functioning in coacheathlete contexts.